Pengaruh Persistensi Laba dan Earning Growth Terhadap Kualitas Laba dengan Corporate Governance Sebagai Variabel Moderasi - Asyifa, Nita Laila; Rosini, Iin; Nofryanti, Nofryanti (Ekonomis: Journal of Economics and Business, 2024)
Income fluctuations cause profit instability, so that the reliability of financial report information is questioned by stakeholders. The aim of this research is to obtain empirical evidence about the influence of earnings persistence and earnings growth on earnings quality with the corporate governance as a moderating variable in companies participating in the CGPI program and listed on the BEI for the 2017-2021 period. The research population consisted of 161 corporate entities and 17 sample companies were selected that met the research criteria for the purposive sampling method. Data processing using the panel data regression method with the Eviews-12 statistical tool. The research results indicate that earnings persistence has a negative effect on earnings quality, while earnings growth has a positive effect on earnings quality. In addition, it was found that corporate governance does not moderate the effect of earnings persistence on earnings quality, but the effect of earnings growth on earnings quality can be moderated by corporate governance.